ANALISIS PENERAPAN STRATEGI PEMBELAJARAN BAHASA INDONESIA BERORIENTASI DEEP LEARNING DI ERA KURIKULUM MERDEKA - Fithriyah, Dewi Niswatul; Aula, Fiki Dzakiyyatul; Nisa, Zumrotun (JEMI, 2025)
Indonesian language learning in the era of the Merdeka Curriculum requires a paradigm shift from mere knowledge transfer to developing higher-order thinking and deep understanding (deep learning). However, in reality, many teachers still implement teacher-centered learning that emphasizes memorization. This study aims to analyze the implementation of deep learning-oriented Indonesian language teaching strategies in grade IV at MI Ulul Albab Bojonegoro. The research employed a qualitative descriptive approach with data collected through observation, in-depth interviews, and documentation. The results show that the teacher has applied learning strategies emphasizing text analysis, reflective discussion, and creative writing tasks contextualized to students’ real-life experiences. The implementation of this strategy enhances student participation, strengthens literacy skills, and fosters critical and reflective thinking. Overall, the deep learning approach has proven effective in creating active, contextual, and meaningful Indonesian language learning aligned with the principles of the Merdeka Curriculum..